EVALUASI PENDIDIKAN DALAM AL-QUR’AN DAN HADIS - Fitriyah Fitriyah; Novi Indriani; Maulidatul Hikmah (STAI Darussalam Lampung, 2024)
This article aims to discuss the evaluation of education in the Qur'an and Hadith. The research is literature, the method of data collection is documentation and the analysis used is content analysis. The results of the study state that evaluation means assessment, assessment is done to measure the results of work. Performance appraisal is an evaluation of behaviour, work performance and potential development that has been done. Evaluation includes two activities, namely measurement and assessment. One thing that characterises evaluation is that the process ends with a decision. This decision concerns the worth and usefulness of the evaluation. In Islamic education, evaluation is one of the components of the Islamic education system that must be carried out systematically and planned as a tool to measure the success or targets to be achieved in the Islamic education process and the learning process. Evaluation of education in Islam can be limited as an activity to determine the progress of a job in the process of Islamic education. The term evaluation as long as traced in the Quran there are several terms that lead to the meaning of evaluation, these terms are al-balâ, al-hisâb, al-hukm, al-qadha, an-nazar, al-imtihân, fatannâ, wazana.